Account Receivable Flow Test to Prove Real Sales Case: A Study Case of a Tax Court Decision in Indonesia - Muhammad Rifky Santoso (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2021)
The data in the financial statements and the corporate tax return must be supported by accurate and valid evidence. When the Directorate General of Taxation (DGT) as a tax authority in Indonesia conducts a tax audit by an account receivable flow test (ARFT), the taxpayer net sales can be corrected to be larger due to a lack of evidence. This paper applied a case study of a tax court decision in Indonesia by a desk-based literature study. The DGT audited a taxpayer and produced a stipulation of additional taxable income. The taxpayer did not agree with the provision and the taxpayer filed an appeal to the tax court. This paper finds the taxpayer’s unorganized and inaccurate bookkeeping leads the judges to reject the taxpayer’s appealing.